Integrated Investigations of Painting Materials in the Sasanian City of Ardaxšīr Khwarrah, near Firuzabad (Southern Iran) - Maria Letizia Amadori; Valeria Mengacci; Pierfrancesco Callieri; Alireza Askari Chaverdi; Matteo Bartolucci; Negar Eftekhari; Alessia Andreotti; Parviz Holakooei (Heritage, 2024)
Ancient Ardaxšīr Khwarrah, today known as Shahr-e Gur, situated near the modern town of Firuzabad in Fars, Iran, holds historical significance as the inaugural capital city of the Sasanian Empire. During archaeological excavations conducted in 2005 by an Iranian–German team directed by Mas‘oud Azarnoush and Dietrich Huff, a mud-brick complex was uncovered, revealing a remarkably well-preserved stretch of wall painting and a polychrome painted floor. The discovery prompted the hypothesis of a potential funerary context dating back to the Sasanian period. Both the wall painting and painted floor have suffered extensive deterioration attributed to the environmental conditions of the archaeological site, which was inscribed on the UNESCO World Heritage List in 2020. To address the urgent need for preservation and further understanding of the site’s artistic and structural elements, an emergency diagnostic project was initiated. Non-invasive investigations were carried out on the wall and floor by optical digital microscopy and portable energy-dispersive X-ray fluorescence. Additionally, representative minute samples underwent analysis through various techniques, including micro-X-ray fluorescence, polarised light microscopy, scanning electron microscopy with energy-dispersive X-ray spectroscopy, micro-Raman spectroscopy, micro-Fourier Transform Infrared Spectroscopy, gas chromatography-mass spectrometry and pyrolysis coupled with gas chromatography-mass spectrometry. The palette of the floor and mural paintings were identified to contain red and yellow ochres, lead-based pigments, carbon black and bone white. The unexpected presence of Egyptian blue mixed with green earth was recognised in the green hues of the wall painting. The detection of protein material in both the wall painting and polychrome floor indicates the use of “a secco” technique, thereby shedding light on the artistic practices employed in Ardaxšīr Khwarrah.